Exploring the relationship between frequent cannabis use, belief updating under uncertainty and psychotic-like symptoms - Liang, Xinyi; Avram, Maria-Mihaela; Gibbs-Dean, Toni; Chesney, Edward; Oliver, Dominic; Wang, Simiao; Obreshkova, Stiliyana; Spencer, Tom; Englund, Amir; Diederen, Kelly (Frontiers in Psychiatry, 2024)
Background: Cannabis users present an important group for investigating putative mechanisms underlying psychosis, as cannabis-use is associated with an increased risk of psychosis. Recent work suggests that alterations in belief-updating under uncertainty underlie psychosis. We therefore compared belief updating under uncertainty between cannabis and non-cannabis users.Methods: 49 regular cannabis users and 52 controls completed the Space Game, via an online platform used for behavioural testing. In the task, participants were asked to predict the location of the stimulus based on previous information, under different uncertainty conditions. Mixed effects models were used to identify significant predictors of mean score, confidence, performance error and learning rate.Results: Both groups showed decreased confidence in high noise conditions, and increased belief updating in more volatile conditions, suggesting that they could infer the degree and sources of uncertainty. There were no significant effects of group on any of the performance indices. However, within the cannabis group, frequent users showed worse performance than less frequent users.Belief updating under uncertainty is not affected by cannabis use status but could be impaired in those who use cannabis more frequently. This finding could show a similarity between frequent cannabis use and psychosis risk, as predictors for abnormal belief-updating.